Regulating algorithmic discrimination through adjudication: the Court of Justice of the European Union on discrimination in algorithmic profiling based on PNR data - Haitsma, Lucas Michael (Frontiers in Political Science, 2023)
This article considers the Court of Justice of the European Union's assessment and regulation of risks of discrimination in the context of algorithmic profiling based on Passenger Name Records data (PNR data). On the June 21, 2022 the court delivered a landmark judgment in Ligue des Droits Humains pertaining to discrimination and algorithmic profiling in a border security context. The CJEU identifies and seeks to regulate several risks of discrimination in relation to the automated processing of PNR data, the manual review of the results of this processing, and the resulting decisions taken by competent authorities. It interpreted whether the PNR Directive that lays down the legal basis for such profiling was compatible with the fundamental right to privacy, the right to data protection, and the right to non-discrimination. In its judgment, the CJEU seems to insufficiently assess various risks of discrimination. In particular, it overlooks risks relating to data quality and representativeness, automation bias, and practical difficulties in identifying discrimination. The judges also seem to prescribe safeguards against discrimination without guidance as to how to ensure their uniform and effective implementation. Such shortcomings can be observed in relation to ensuring the non-discriminatory nature of law enforcement databases, preventing indirectly discriminatory profiling practices based on collected PNR data, and configuring effective human-in-the-loop and transparency safeguards. This landmark judgement represents an important step in addressing algorithmic discrimination through CJEU adjudication. However, the CJEUs inability to sufficiently address the risks of discrimination in the context of algorithmic profiling based on the PNR Directive raises a broader concern. Namely, whether the CJEU is adequately equipped to combat algorithmic discrimination in the broader realm of European border security where algorithmic profiling is becoming increasingly commonplace.